Effects of Resting vs. Continuous Blood-Flow Restriction-Training on Strength, Fatigue Resistance, Muscle Thickness, and Perceived Discomfort - Schwiete, Carsten; Franz, Alexander; Roth, Christian; Behringer, Michael (Frontiers in Physiology, 2021)
The purpose of this study was to clarify whether blood-flow restriction during resting intervals (resting blood-flow restriction, rBFR) is comparable to a continuous BFR training (cBFR) regarding its effects on maximum strength, hypertrophy, fatigue resistance, and perceived discomfort. 19 recreationally trained participants performed four sets (30-15-15-15 repetitions) with 20% 1RM on a 45° leg press twice a week for six weeks (cBFR, n=10; rBFR, n=9). Maximum strength, fatigue resistance, muscle thickness and girth were assessed at three timepoints (pre, mid, post). Subjective pain and perceived exertion were determined immediately after training at two timepoints (mid, post). Maximum strength (p < .001), fatigue resistance (p < .001), muscle thickness (p < .001), and girth (p = .008) increased in both groups over time with no differences between groups (p > .05). During the intervention, the rBFR group exposed significantly lower perceived pain and exertion values compared to cBFR (p < .05). rBFR training led to similar gains in strength, fatigue resistance and muscle hypertrophy as cBFR training while provoking less discomfort and perceived exertion in participants. In summary, rBFR training could provide a meaningful alternative to cBFR as this study showed similar functional and structural changes as well as less discomfort.